Enhanced electrochemical properties of sodium‐doped lithium‐rich manganese‐based cathode materials. Issue 1 (19th January 2021) - Fang, T.; Zhu, Y.; Hua, J.; Chu, H.; Qiu, S.; Zou, Y.; Xiang, C.; Xu, F.; Sun, L.
Abstract: In this work, sodium has been successfully doped into the layered lithium‐rich manganese‐based cathode material through melt impregnation. The as‐prepared samples are characterized by multiple techniques of x‐ray diffraction, scanning electron microscopy, transmission electron microscopy, x‐ray photoelectron spectroscopy and the electrochemical measurements. The results show that sodium doping hardly changes the layered structure and surface morphology of pristine sample. The sample particles of sodium‐doped materials exhibit polygonal shape similar to prism. The sodium‐doped material possesses high rate performance and good cycling stability, and the initial charge and discharge capacity reaches 340.2 mA h g −1 and 249.0 mA h g −1 at a current density of 20 mA g −1, respectively. The initial coulombic efficiency of the first cycle is 73 %. After running 100 repeated cycles at 40 mA g −1 and 100 mA g −1, the discharge capacity could still be maintained at about 230.0 mA h g −1 and 220.0 mA h g −1, respectively. Moreover, the voltage attenuation is effectively suppressed during charging/discharging cycles. Abstract : Sodium ions are doped into lithium‐rich manganese‐based cathode materials (LMNO) through melt impregnation, which exhibits high initial discharge capacity and superior cycling and rate performance. Moreover, the voltage attenuation is also suppressed by sodium doping during the repeated cycles.